Stability analysis of an embankment resting upon a column-reinforced soil - Jellali, B.; Bouassida, M.; de Buhan, P. (International journal for numerical and analytical methods in geomechanics, 2011)
The design against failure of an embankment resting upon a soft soil improved by a group of columns is investigated with the help of the yield design homogenization approach. Assuming that both constituents of the reinforced ground are purely cohesive materials (‘lime column’ technique), an upper bound estimate for the macroscopic strength condition of the reinforced soil as a homogenized medium is first obtained, providing definite evidence of a shear strength anisotropy associated with the reinforcement preferential orientation. The kinematic method of yield design is then performed on the basis of such a criterion, making use of rotational failure mechanisms involving slip circles in the reinforced ground. Upper bound estimates are finally obtained for the embankment stability factor, as functions of the degree of reinforcement and relative thickness of the soil layer. These results are compared with those derived from a simplified analysis, where the reinforced soil is assumed to exhibit an averaged isotropic cohesion. This comparison clearly indicates that the latter simplified analysis may produce quite unsafe estimates for the embankment stability, which can be attributed to the fact that it fails to capture the inherent strength anisotropy of the reinforced soil. Copyright © 2010 John Wiley & Sons, Ltd.